2021
DOI: 10.3390/nano11081933
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Magnetic Properties of Building Blocks of Mn and Fe Atomic Chains on Nb(110)

Abstract: We present results for the electronic and magnetic structure of Mn and Fe clusters on Nb(110) surface, focusing on building blocks of atomic chains as possible realizations of topological superconductivity. The magnetic ground states of the atomic dimers and most of the monatomic chains are determined by the nearest-neighbor isotropic interaction. To gain physical insight, the dependence on the crystallographic direction as well as on the atomic coordination number is analyzed via an orbital decomposition of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 44 publications
(75 reference statements)
7
15
0
Order By: Relevance
“…The magnetic ground states derived from the new ab-initio optimization technique are compared to those obtained from spin models parametrized from first principles and the effect of the different kind of spin-spin interactions is discussed. Further applications are presented for Fe chains deposited on the (110) surface of bodycentered cubic (bcc) Nb and on the (0001) surface of hexagonal closed pack (hcp) Re, where spin-spiral ground states are found in agreement with previous theoretical works [25,39] and experiment [4].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The magnetic ground states derived from the new ab-initio optimization technique are compared to those obtained from spin models parametrized from first principles and the effect of the different kind of spin-spin interactions is discussed. Further applications are presented for Fe chains deposited on the (110) surface of bodycentered cubic (bcc) Nb and on the (0001) surface of hexagonal closed pack (hcp) Re, where spin-spiral ground states are found in agreement with previous theoretical works [25,39] and experiment [4].…”
Section: Introductionsupporting
confidence: 71%
“…Using the Vienna Ab-initio Simulation Package (VASP) [56] Laszloffy et al [39] found that by putting an Fe adatom on the (110) surface of Nb, the average vertical distance of the atoms in the two uppermost Nb layers decreased to 2.2542 Å from the bulk value of 2.3337 Å , while the vertical distance between the Fe adatom and the closest Nb atoms decreased to 1.9868 Å. In the calculations of atomic clusters of Fe these values were used for the interlayer distances between the uppermost two Nb layers, as well as between the top Nb layer and the first two vacuum layer, in which the Fe atoms were embedded [39], respectively. We adopted this geometry in our present calculations of the Fe chains in terms of the embedding Green's function technique.…”
Section: Fe Chains On Nb(110) and Re(0001)mentioning
confidence: 99%
“…Here we consider the [1 10] and the [1 11] dimers only. Based both on experiments on short Mn chains on Nb(110) [21] and on ab initio calculations [22] it is suggested that the coupling of the Mn atoms in the [1 10] dimer is ferromagnetic (FM), while in the [1 11] dimer it is antiferromagnetic (AFM).…”
Section: B Mn Dimers On Nb(110)mentioning
confidence: 99%
“…The theoretical study of Lászlóffy et al [22] suggests that a slightly noncollinear and/or canted configuration can exist for the dimers in the normal state. The possibility of the formation of such tilted ground states and the lack of split YSR states in the AFM dimer compared to experiments motivated us to study the effect of the noncollinear spin configurations to the YSR states.…”
Section: B Mn Dimers On Nb(110)mentioning
confidence: 99%
See 1 more Smart Citation